Genetic analysis of muscular dystrophies: our experience in Mexico - Escobar-Cedillo, Rosa Elena; López-Hernández, Luz; Miranda-Duarte, Antonio; Curiel-Leal, María Dolores; Suarez-Ocón, Andrea; Sánchez-Chapul, Laura; Berenice Luna-Angulo, Alexandra; Ávila-Ramírez, Guillermina; López-Hernández, Julia Angélica; Gómez-Díaz, Benjamín (Folia Neuropathologica, 2021)
Muscular dystrophies are a group of well-defined genetic disorders characterized by the variable distribution of muscle wasting and progressive weakness. The diagnosis and treatment of these diseases remain challenging due to genetic heterogeneity and clinical overlapping. Herein, we describe our 10 years’ experience with the diagnosis and management of muscular dystrophy patients. In total, 169 patients were screened for pathogenic variants in eleven genes linked to frequent muscular dystrophies using MLPA and NGS sequencing panels. Most frequent muscular dystrophies found in the Mexican population were dystrophinopathies, dysferlinopathies and calpainopathies. Novel variants were found in genes: DMD, CAPN3, DYSF, and FKRP. For Duchenne muscular dystrophy, improvements in early diagnosis and prolonged ambulation were achieved, on the contrary, for limb-girdle muscular dystrophies and congenital muscular dystrophies, uncomplimentary follow-up and lack of detection strategies were observed. For most common muscular dystrophies, improvements in diagnosis and management have been achieved in the last 10 years, due to a collaborative effort done nationwide.